IMPACT OF INTERNATIONAL PRESENCE ON SERVICE SUPPLY CHAIN QUALITY - Adelina Gnanlet; H. Muge Yayla-Kullu (International Journal of Supply Chain Management, 2013)
In this paper, we study the implications of international operations on the quality of airline service supply chain at the regional level. As a first study, we take an operations viewpoint of how well the work is done and explore multiple quality dimensions of the service supply chain at both international and regional level. In particular, we study the service quality of supplier (ground) services, in-flight products, in-flight entertainment systems, and flight attendants efficiencies. We use a global airlines dataset and quality assessments provided by a renowned quality-audit organization to test our hypotheses. We find that when an airline serves international market segment in addition to its regional operations, the quality of the service supply chain also gets better in the regional market. When managers design and manage service quality expectations in multiple market segments, service quality expectations in higher market segment influences the service quality in lower market segment.